Octa carboxy metal (II) phthalocyanine covalent films as pH sensitive electrochemical sensor for neurotransmitters - Moyo, Iphithuli (Rhodes University, Faculty of Science, Department of Chemistry)
Octa acyl chloride metallophthalocyanines of cobalt (CoOAClPc) and iron (FeOAClPc) were synthesized and characterized using spectroscopic and electrochemical techniques. The metallophthalocyanines were fabricated as thin films onto phenylethylamine (PEA) pre-grafted Au electrode following a covalent amide reaction. The spectroscopic and electrochemical characterization confirmed the modification of the bare Au with PEA monolayer thin film (Au-PEA) and the covalent immobilization of MOAClPc to yield Au-PEA-MOAClPc (where M is Co and Fe). The acyl chloride functional groups were hydrolyzed forming pH sensitive thin films of terminal carboxylic acid (-COOH) functional groups (Au-PEA-MOCAPc). The Au-PEA-MOCAPc electrode exhibited pH selectivity and sensitivity properties towards the negatively charged [Fe(CN)6]3-/4- and positively charged [Ru(NH3)6]2+/3+ redox probes. The Au-PEA-MOCAPc electrodes were studied for their electrocatalytic and electroanalytical properties towards the detection of catecholamine neurotransmitters; dopamine (DA), epinephrine (EP) and norepinephrine (NOR). The electrodes were further investigated in the screening of ascorbic and uric acids by means of pH sensitive functional groups. The modification process exhibited good reproducibility. Excellent electrocatalytic and electroanalytical properties were observed. The limits of detection (LOD) determined using 3Ïƒ/m was found to be 64 nM, 0.22 Î¼M and 0.17 Î¼M for DA, EP and NOR respectively using Au-PEA-CoOCAPc. For Au-PEA-FeOCAPc, the LOD was found to 0.24 Î¼M, 0.45 Î¼M and 0.34 Î¼M for DA, EP and NOR respectively. The Au-PEA-MOCAPc electrodes screened off the strong interferents, ascorbic and uric acid. The Au-PEA-FeOCAPc electrode was evaluated for its potential application in real sample analysis using new born calf serum, and it showed excellent percentage recoveries.
Keywords: Phthalocyanines; Thin films; Neurotransmitters; Carboxylic acids